Reflection on the Spirit of Heroism at the Flag Ceremony for the Commemoration of National Santri Day - Ali Mu'tafi; Robingun Suyud Elsyam; Salis Irvan Fuadi (Lembaga Pendidikan Hikmatun Najah Blora, 2023)
The article aims to reflect on the spirit of heroism at the flag ceremony for the commemoration of National Santri Day, by focusing on the values contained in these activities. This research uses mixed methods, a combination of qualitative and quantitative research conducted on Islamic boarding schools in Indonesia. Data were obtained through activity documents as well as printed and online literature and then analyzed descriptively. The research concluded: that the flag ceremony commemorating the national santri day makes a reflection of the spirit of heroism manifesting an attitude of heroic spirit which includes: faith and piety to God Almighty, love for the motherland, placing the interests of the nation above personal or group interests, upholding the truth and justice, upholding human dignity and worth, and being sincere and selfless. The spirit of heroism is very important to be internalized in shaping the national character. Research has implications for strengthening the spirit of heroism in Islamic boarding schools and other educational institutions. This research is expected to contribute to strengthening character values.